2016
DOI: 10.1111/jsr.12368
|View full text |Cite
|
Sign up to set email alerts
|

Reduced evoked motor and sensory potential amplitudes in obstructive sleep apnea patients

Abstract: Summary It is unknown to what extent chronic intermittent hypoxaemia in obstructive sleep apnea causes damage to the motor and sensory peripheral nerves. It was hypothesized that patients with obstructive sleep apnea would have bilaterally significantly impaired amplitudes of both motor and sensory peripheral nerve‐evoked potentials of both lower and upper limbs. An observational study was conducted on 43 patients with obstructive sleep apnea confirmed by the whole‐night polysomnography, and 40 controls to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Our study shows a relationship among axonal neuropathy, hypoxia parameters and nerve conduction in OSA patients, which is consistent with previous reports (9,10,13). These studies also reported that subjects with severe OSA, min SaO 2 ≤80%, and ST 90 have lower amplitude for sensory and mixed nerve action potentials, and that sural nerve velocity is slower in OSA patients (8,9).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study shows a relationship among axonal neuropathy, hypoxia parameters and nerve conduction in OSA patients, which is consistent with previous reports (9,10,13). These studies also reported that subjects with severe OSA, min SaO 2 ≤80%, and ST 90 have lower amplitude for sensory and mixed nerve action potentials, and that sural nerve velocity is slower in OSA patients (8,9).…”
Section: Discussionsupporting
confidence: 93%
“…Prevalence of polyneuropathy due to chronic hypoxia have been reported in a similar range of 28% to 70% in patients with OSA and COPD (5,(9)(10)(11). Previous studies have reported that peripheral nerve sensory amplitudes are impaired in OSA patients, but the relationship with hypoxemia has not been fully elucidated (9,12,13). We hypothesized that patients with severe OSA and hypoxia show significantly impaired peripheral nerve conduction compared to controls.…”
Section: Introductionmentioning
confidence: 91%
“…[3][4][5] OSAS is associated with a range of medical conditions such as hypertension, obesity, type 2 diabetes, depression, peripheral neuropathy, as well as with psychological and cognitive deficits. [4][5][6][7][8][9][10] However, the pathophysiologic mechanisms of OSAS are still challenging to disentangle. Transcranial magnetic stimulation (TMS) studies proposed an altered motor cortical excitability as part of the mechanisms underlying OSAS in terms of a dysfunctional cortico-motoneuronal system.…”
Section: Introductionmentioning
confidence: 99%
“…But is the neuropathy of OSAS, the cause or a consequence of the disease? It is unknown to what extent chronic intermittent hypoxemia in OSAS causes damage to the motor and sensory peripheral nerve, but muscle action potential and sensory nerve action potential amplitudes are significantly reduced in the nerves outside UA in patients with OSAS suggesting that axonal damage exists in patients with OSAS to a greater extent than previously thought [24]. On the other hand, association between OSAS and sensory neuropathy, and nerve damage outside the UA [18,[25][26][27], type 2 or type 1A diabetic neuropathy, and axonal subtypes of Charcot-Marie-Tooth disease [28][29][30][31] has been also demonstrated.…”
Section: The Neurological Theory Of Osas and The Upper Airways Remodementioning
confidence: 58%